Outstaffing in sport - B. Anikin; O. Anikin (Вестник университета)
The subject of research in the article is the use of the concept outstaffing in sports. The development concept is called in the initial stage. With regard to its use in sport, the publications on this subject virtually absent. The purpose of the study is to identify the results obtainfrom the use of the concept of specific sports teams, leagues and countries.